The Effect of Firm Size and Pofitabilitty on Audit Delay in Manufacturing Comparies Listed on the Indonesia Stock exchange for the 2022-2024 Period - Lela Listi Bahati; Ade Imam Muslim (Hikamatzu | Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of firm size and profitability on audit delay in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. The study employs a quantitative method with a panel data approach. The study population consists of 90 sample companies, with the research comprising 35 manufacturing companies selected using purposive sampling, resulting in 105 observations. Data analysis was conducted using the EViews 12 application. The data used are secondary data obtained from the companies’ annual financial statements. Firm size is measured by total assets, profitability is measured using Return on Assets (ROA), and audit delay is calculated based on the number of days between the financial statement date and the auditor’s report date. Data analysis is conducted using panel data regression with a fixed effects model. The results indicate that firm size has a negative and significant effect on audit delay, while profitability is proven to have a significant effect on audit delay.